Novel antimicrobial applications of copper oxide nanoparticles after combination with tissue conditioner used in complete prostheses - Saeed Nikanjam; Aria Yeganegi; Mohammad-Yousef Alikhani; Abbas Farmany; Seyed Amir Ghiasian; Roghayeh Hasanzade (BMC, 2024)
Abstract Background Tissue conditioners are used for treating and improving the tissues supporting complete dentures. On the other hand, recent advances in nanotechnology have revolutionized various fields of science, including dentistry. The present study aimed to investigate novel antimicrobial applications of copper oxide nanoparticle-based tissue conditioner used in complete prostheses. Methods The present experimental study included 126 tissue conditioner samples with different concentrations of copper oxide nanoparticles (20%, 10%, 5%, 2.5%, 1.25%, 0.625%, and 0% w/w). The samples were incubated with Enterococcus faecalis, Pseudomonas aeruginosa, and Candida albicans in 24-well plates for 24 h. Then, samples from the wells were re-incubated for 24 h, and the microorganisms were counted. Results The culture media containing E. faecalis and P. aeruginosa showed significantly different growth between different nanoparticle concentrations following 24 h (P < 0.001), showing a reduction in bacterial growth with increased nanoparticle concentration. Both bacteria did not show any growth at the 20% concentration. However, C. albicans showed significant differences in growth between different nanoparticle concentrations following 48 h (P < 0.001), showing a reduction in growth with increased nanoparticle concentration. Also, the least growth was observed at the 20% concentration. Conclusions In conclusion, the CuO nanoparticles were prepared using a green synthesis methon in the suitable sizes. Moreover, the tissue conditioners containing CuO nanoparticles showed acceptable antimicrobial properties against E. faecalis, P. aeruginosa, and C. albicans.